The evolution of the barred galaxy population in the TNG50 simulation - Rosas-Guevara, Yetli; Bonoli, Silvia; Dotti, Massimo; Izquierdo-Villalba, David; Lupi, Alessandro; Zana, Tommaso; Bonetti, Matteo; Nelson, Dylan; Springel, Volker; Hernquist, Lars; Vogelsberger, Mark (Monthly notices of the Royal Astronomical Society, 2022)
We use the magnetic-hydrodynamical simulation TNG50 to study the evolution of barred massive disc galaxies. Massive spiral galaxies are already present as early as z = 4, and bar formation takes place already at those early times. The bars grow longer and stronger as the host galaxies evolve, with the bar sizes increasing at a pace similar to that of the disc scalelengths. The bar fraction mildly evolves with redshift for galaxies with $M_{*}\ge 10^{10}\rm M_{\odot }$, being greater than $\sim 40{{\ \rm per\ cent}}$ at 0.5 < z < 3 and $\sim 30{{\ \rm per\ cent}}$ at z = 0. When bars larger than a given physical size ($\ge 2\, \rm kpc$) or the angular resolution limit of twice the I-band angular PSF FWHM of the HST are considered, the bar fraction dramatically decreases with increasing redshift, reconciling the theoretical predictions with observational data. We find that barred galaxies have an older stellar population, lower gas fractions, and star formation rates than unbarred galaxies. In most cases, the discs of barred galaxies assembled earlier and faster than the discs of unbarred galaxies. We also find that barred galaxies are typical in haloes with larger concentrations and smaller spin parameters than unbarred galaxies. Furthermore, the inner regions of barred galaxies are more baryon-dominated than those of unbarred galaxies but have comparable global stellar mass fractions. Our findings suggest that the bar population could be used as a potential tracer of the buildup of disc galaxies and their host haloes. With this paper, we release a catalogue of barred galaxies in TNG50 at six redshifts between z = 4 and 0.